APPLICATION OF IN SILICO STUDIES TARGETING TELOMERIC G-QUADRUPLEX COMPLEX BY PERYLENE DIIMIDES FOR ANTICANCER THERAPY - Cn, Hemalatha; M, Vijey Aanandhi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Telomerase enzyme which is expressed in detectable levels and its mechanism was that it increases the length when it binds to telomeres. This eventually leads to extension of lifespan of cells and also makes an attractive target for cancer therapy. Perylene diimides bind to telomerase with duplex genomic DNA, and these G-quadruplex ligands are of responsible for binding affinity with respective proteins. Based on the IC50 values of perylene diimides, QSAR has been studied out and the results are elaborated in preliminary research works. From the results of QSAR, the selected perylene ligands are selected for docking choosing telomerase as a target/protein. From the results of in silico studies, new compounds are designed and synthesized accordingly. Now, the objective of the study was to dock the final synthesized compounds with the telomerase protein to study regarding the pKi value using G-quadruplex ligand database (G4LDB). The docked results are visualized using Discovery Studio Visualizer 4.1. The results are compared with the standard N,N'-bis-(2-(1-piperidino)ethyl)-3,4,9,10-perylene tetracarboxylic acid diimide (PIPER) drug and these compounds will be effective for anticancer therapy. Methods: The study was to investigate the docking results of synthesized perylene compounds with the results from G4LDB and visualized by Discovery Studio 4.1 Visualizer. The telomerase proteins selected for the study were extracted from Protein Data Bank, and the proteins selected for the study are 3SC8 and 3CE5. Among the compounds (R1, R2, R3, and R4) screened in G-Quadruplex Ligand Database, compound R3 shows better binding affinity with good pKi value as well the interactions with the protein and ligand show better affinity with the targets and these are compared with the standard drug PIPER drug. Results: Compound R3 possesses the best binding affinity with the target 3CE5 and 3SC8 which shows that the compound will be effective for anticancer therapy.